2008
DOI: 10.1016/j.biopsych.2007.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Cingulate-Precuneus Interactions: A New Locus of Dysfunction in Adult Attention-Deficit/Hyperactivity Disorder

Abstract: Background-Pathophysiological models of Attention-Deficit/Hyperactivity Disorder (ADHD) have focused on frontal-striatal circuitry with alternative hypotheses relatively unexplored. Based on evidence that negative interactions between frontal foci involved in cognitive control and the nongoal directed 'default-mode' network prevent attentional lapses, we hypothesized abnormalities in functional connectivity of these circuits in ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

81
625
12
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 788 publications
(731 citation statements)
references
References 40 publications
81
625
12
13
Order By: Relevance
“…Although they were selected carefully according to ADHD symptom scores, both from self-report and the rating of one of their close friends or relatives, they may not show altered resting brain activity to the same degree as individuals with a clinical diagnosis of ADHD. Despite this result, the potential connection between waiting difficulty and disruptions of default mode brain system could not be ruled out as both deficits have been repeatedly found in patients with ADHD (Castellanos et al, 2008;Luman et al, 2005). Further, prospective planning, underpinned by DMN activity, appears to play a role in waiting abilities.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although they were selected carefully according to ADHD symptom scores, both from self-report and the rating of one of their close friends or relatives, they may not show altered resting brain activity to the same degree as individuals with a clinical diagnosis of ADHD. Despite this result, the potential connection between waiting difficulty and disruptions of default mode brain system could not be ruled out as both deficits have been repeatedly found in patients with ADHD (Castellanos et al, 2008;Luman et al, 2005). Further, prospective planning, underpinned by DMN activity, appears to play a role in waiting abilities.…”
Section: Discussionmentioning
confidence: 95%
“…For example, patients with ADHD exhibit altered functional connectivity at rest and during task performance. They also display reduced task-induced attenuation of VLF oscillations in regions linked to DMN (Castellanos et al, 2008;Fair et al, 2010;Fassbender et al, 2009;Liddle et al, 2011;Tian et al, 2008). In line with neuroimaging findings, studies with DC-EEG have found reduced resting state VLF EEG power in adolescents with ADHD, along with decreased rest-to-task attenuation of VLF EEG power compared to healthy age-matched volunteers (Helps et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the current paper we provide the first test of this hypothesis by exploring the intrinsic organization of DMN, DAN, VAN and SN and their interactions in adults with ADHD by evaluating patterns of BOLD signal correlations measured during rest [32,35,36]. Prior resting state studies have found reduced connectivity in ADHD between DMN regions [37][38][39]; for opposite findings see Tian et al, [40], McCarthy 5 et al, [41], as well as altered organisation of DAN and VAN [21,41,42]. However, no study has directly explored connectivity within and between the DMN, DAN, VAN and SN in ADHD.…”
Section: Introductionmentioning
confidence: 94%
“…ADHD adults [44,45] and in children with ADHD [46] . Besides, abnormalities in the inter-regional synchronization between the cognitive-attentional network and default network have been reported in ADHD patients [14,44] .…”
mentioning
confidence: 99%
“…Besides, abnormalities in the inter-regional synchronization between the cognitive-attentional network and default network have been reported in ADHD patients [14,44] . Thus we hypothesized that the mainly decreased local activity found in the current study in regions of the cognitive-attentional network and the default network of ADHD children may be associated with altered functional synchronization between them, which may underlie the attention lapses in ADHD [47] .…”
mentioning
confidence: 99%